Mycovirus Diversity and Evolution Revealed/Inferred from Recent Studies - Kondo, Hideki; Botella, Leticia; Suzuki, Nobuhiro (Annual review of phytopathology, 2022)
High-throughput virome analyses with various fungi, from cultured or uncultured sources, have led to the discovery of diverse viruses with unique genome structures and even neo-lifestyles. Examples in the former category include splipalmiviruses and ambiviruses. Splipalmiviruses, related to yeast narnaviruses, have multiple positive-sense (+) single-stranded (ss) RNA genomic segments that separately encode the RNA-dependent RNA polymerase motifs, the hallmark of RNA viruses (members of the kingdom ). Ambiviruses appear to have an undivided ssRNA genome of 3∼5 kb with two large open reading frames (ORFs) separated by intergenic regions. Another narna-like virus group has two fully overlapping ORFs on both strands of a genomic segment that span more than 90% of the genome size. New virus lifestyles exhibited by mycoviruses include the yado-kari/yado-nushi nature characterized by the partnership between the (+)ssRNA yadokarivirus and an unrelated dsRNA virus (donor of the capsid for the former) and the hadaka nature of capsidless 10-11 segmented (+)ssRNA accessible by RNase in infected mycelial homogenates. Furthermore, dsRNA polymycoviruses with phylogenetic affinity to (+)ssRNA animal caliciviruses have been shown to be infectious as dsRNA-protein complexes or deproteinized naked dsRNA. Many previous phylogenetic gaps have been filled by recently discovered fungal and other viruses, which have provided interesting evolutionary insights. Phylogenetic analyses and the discovery of natural and experimental cross-kingdom infections suggest that horizontal virus transfer may have occurred and continue to occur between fungi and other kingdoms. Expected final online publication date for the , Volume 60 is August 2022. Please see http://www.annualreviews.org/page/journal/pubdates for revised estimates.